Unraveling the Financial Impact of ESG Performance: Evidence from NSE Listed Companies in India - Mazumder, Sayantan Guha; Dey, Pranay; Bora, Jutimala; Bora, Toralima (International Journal of Economics and Financial Issues, 2025)
In the present corporate world, as social and environmental concerns about corporate resource management and economic operations have grown, sustainability has become increasingly important, leading to a re-examination of the ethical dimensions of business. As such, businesses are attempting to be socially responsible by using a dualistic strategy that strikes a balance between social responsibility and welfare and financial performance. Environmental, Social and Governance (ESG) is one such yardstick which promotes social responsibility and welfare. The present study attempts to assess whether ESG parameters influence the financial outcomes of National Stock Exchange (NSE) listed companies in India. To validate the results, ADF Unit Root Test, Granger Causality Test and Regression Models have been used. The results reveal that the individual ESG scores showcased a positive influence on financial performance and the overall ESG scores displayed a mixed and insignificant influence on the financial performance.